Screening Tools and Assessment Methods of Cognitive Decline Associated With Age-Related Hearing Loss: A Review - Yue, Tao; Chen, Yu; Zheng, Qi; Xu, Zihao; Wang, Wei; Ni, Guangjian (Frontiers in Aging Neuroscience, 2021)
A growing number of cross-sectional and longitudinal studies confirm strong links between hearing and cognitive function. It has been proven that elders with age-related hearing loss (ARHL) have a significantly higher cognitive impairment incidence than those with normal hearing. The correlation mechanism between the ARHL and cognitive decline has not yet been fully elucidated. However, auditory intervention for patients with ARHL may reduce the risk of cognitive decline since early cognitive screening may improve related treatment strategies. Currently, clinical audiology examinations rarely include cognitive screening tests. One of the reasons is that there is still a lack of objective quantitative indicators with high sensitivity and specificity. Questionnaires are currently widely used as a cognitive screening tool, but the performance may be negatively affected by hearing loss. Many electroencephalogram (EEG) and magnetic resonance imaging (MRI) studies analyzed brain structure and function changes in patients with ARHL. These objective electrophysiological tools provide a possibility further to discover the association mechanism between auditory and cognitive function, which may also find biological markers to be more extensively applied in observing the effects of rehabilitation training for patients with ARHL. We reviewed the clinical manifestations, pathological changes, and causes of ARHL and discussed their cognitive function effects. Specifically, we focused on the current cognitive screening tools and assessment methods and analyzed each method’s limitations and potential integration.